2023
DOI: 10.1038/s41380-023-02173-1
|View full text |Cite
|
Sign up to set email alerts
|

White matter alterations in Attention-Deficit/Hyperactivity Disorder (ADHD): a systematic review of 129 diffusion imaging studies with meta-analysis

Abstract: Aberrant anatomical brain connections in attention-deficit/hyperactivity disorder (ADHD) are reported inconsistently across diffusion weighted imaging (DWI) studies. Based on a pre-registered protocol (Prospero: CRD42021259192), we searched PubMed, Ovid, and Web of Knowledge until 26/03/2022 to conduct a systematic review of DWI studies. We performed a quality assessment based on imaging acquisition, preprocessing, and analysis. Using signed differential mapping, we meta-analyzed a subset of the retrieved stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 155 publications
0
11
0
Order By: Relevance
“…In previous studies, the researchers found that ADHD patients had abnormal development of gray matter in the basal ganglia, abnormal development of white matter in the frontal and temporal lobes of the brain, and abnormal brain network connections (Cortese et al., 2021; De La Fuente et al., 2013; Gagnon et al., 2022; Klein et al., 2021; Parlatini et al., 2023; Schmithorst et al., 2016; Vilgis et al., 2016; Wu et al., 2020; Zhao et al., 2020, 2022). In this study, we found white matter abnormalities in frontal lobe, temporal lobe, and other brain areas in ADHD children, we also found gray matter abnormalities in caudate nucleus in ADHD children.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the researchers found that ADHD patients had abnormal development of gray matter in the basal ganglia, abnormal development of white matter in the frontal and temporal lobes of the brain, and abnormal brain network connections (Cortese et al., 2021; De La Fuente et al., 2013; Gagnon et al., 2022; Klein et al., 2021; Parlatini et al., 2023; Schmithorst et al., 2016; Vilgis et al., 2016; Wu et al., 2020; Zhao et al., 2020, 2022). In this study, we found white matter abnormalities in frontal lobe, temporal lobe, and other brain areas in ADHD children, we also found gray matter abnormalities in caudate nucleus in ADHD children.…”
Section: Discussionmentioning
confidence: 99%
“…Byeong-Yeul Lee and his team identified a reduction in the body of the corpus callosum through thickness analysis 91 , while Deniz Sigirli and his team found significant changes in the posterior midbody of the corpus callosum through shape analysis 92 . A large meta-analysis encompassing 32 datasets (26 involving children and 6 involving adults) showed that one of the most significant and consistent white matter changes in ADHD patients is the reduced FA value in the body of the corpus callosum 93 . These studies suggest that changes in the corpus callosum body fibers are a common pathological feature of both diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent systematic review included 129 diffusion-weighted imaging studies of ADHD and reported alterations in diffuse brain connectivity, most consistently in the splenium and body of the corpus callosum. 6 The review highlighted that most studies have focused on frontostriatal networks, in line with a dominant pathophysiological hypothesis of ADHD. Further, only one-fifth of studies restricted recruitment to adults.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 The neurobiological characteristics underlying symptom severity, associated cognitive deficits, and treatment response in adults require further study. 3 , 6 Imaging studies have identified alterations in brain anatomy and function among people with ADHD compared with neurotypical controls, although these have mainly focused on children. Observed alterations include reduced volume of the basal ganglia and frontocingulate cortex, 7 , 8 and hypoactivation of frontostriatal regions during inhibition tasks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation